Identification of Salvia miltiorrhiza germplasm resources based on metabolomics and DNA barcoding - He, Gaojie; Man, Jinhui; Chen, Ying; Zhang, Xiaoqin; Wang, Xin; An, Kelu; Amu, Laha; Chen, Wenqin; Wang, Baowei; Shi, Yue; Wang, Xiaohui; Wei, Shengli (Frontiers in Pharmacology, 2025)
IntroductionSalvia miltiorrhiza radix et rhizoma (Danshen) is a crucial medicinal material for treating cardiovascular and cerebrovascular diseases. However, the presence of adulterants and intraspecific variability poses challenges to its clinical safety.MethodsThis study collected samples of S. miltiorrhiza from various regions and commonly encountered adulterants. The composition differences of S. miltiorrhiza radix and its adulterants were analyzed by fingerprint and broad-target metabolomics. Chloroplast genome was used to distinguish intra-genus species and DNA barcoding was used to identify germplasm sources.ResultsThe fingerprinting analysis proved that there is no chemical composition consistency between S. miltiorrhiza radix and its adulterants. Broad-targeted metabolomics can distinguish S. miltiorrhiza radix from Salvia yunnanensis radix, Dipsacus asperoides radix, and Arctium lappa radix. Additionally, comparative chloroplast genome analysis indicated that atpF and rps4-trnT-UGU were the potential DNA barcodes for S. miltiorrhiza. 259 samples from 13 provinces and 21 origins were amplified and sequenced, resulting in the identification of 62 haplotypes. The unique haplotypes found in Shanxi Luoyang, Shandong Qingdao and other places can be used as molecular geographic markers for the identification of the germplasm source of S. miltiorrhiza.DiscussionThis study systematically differentiates S. miltiorrhiza from its adulterants and highlights the potential of unique haplotypes as markers for sourcing. The findings provide strong scientific evidence for the clinical safety of S. miltiorrhiza, emphasizing the importance of proper cultivation, selection, and breeding of varieties.